Role of H-bond formation in the photoreactivity of curcumin. Issue 2 (2008) - Nardo Nardo, Luca Luca; Paderno Paderno, Roberta Roberta; Andreoni Andreoni, Alessandra Alessandra; Másson Másson, Már Már; Haukvik Haukvik, Tone Tone; TØnnesen TØnnesen, Hanne Hjorth Hanne Hjorth
Abstract : Curcumin is the main constituent of curry. In its ground state it shows chemo-preventive, chemo-therapeutic and anti-inflammatory effects. For its immunostimulating action it has been considered for the development of drugs suitable for treating AIDS and cystic fibrosis. Further biological action is induced in curcumin by photoactivation: in suitable environmental conditions electronically excited curcumin can act as a singlet oxygen generator. Moreover, cytotoxicity is enhanced by light exposure and antibacterial effects are photosensitized. This work is aimed to understand the photobiological action of curcumin by elucidating the deactivation mechanisms of its first excited singlet state. In particular we find evidence of the role of tautomerization in the excited state by measuring fluorescence lifetimes and quantum yields for such compound dissolved in solvents of different polarity and H-bonding capability. Degradation quantum yield and singlet oxygen generation efficiency were also measured in acetonitrile and methanol. The results emphasize the strong dependence of the deactivation processes from the environment. The deactivation phenomenology can be fully explained by postulating intramolecular proton transfer in the cis enol conformer to be the leading non-radiative deactivation pathway.